PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI KOPI PROSES JENIS ROBUSTA DAMPIT - Eko Imam Prastiadi; Wahu Hidayat Riyanto; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2019)
Coffee has a superior product potential and with the existence of this farming business is quite helpful in terms of employment and reducing the unemployment rate. And efforts to increase coffee farmers' incomes are goals that must be achieved. This study aims to determine how much influence the variables that can affect the production of Robusta coffee. In this study using a questionnaire method. The sampling technique used was positive sampling with 37 farmers who were able to process coffee well. Based on the regression analysis of the Cobb-Douglas production function model that explains LnQ = LnA + αLnK + βLnL shows the variable capital (6,555) and labor (2,055) in one season has a significant effect on coffee production. Every 1% increase in land area will increase coffee production by 6.555%. Every increase of labor by 1% will cause an increase in coffee production by 2,055%. Statistical analysis shows the coefficient of determination (R2) is 0.58 and the value of the F-statistic test probability is significant at α= 5%